Pengaruh Suhu Pencampuran dan Lama Pengadukan terhadap Karakteristik Sediaan Krim - Baskara, Ida Bagus Bas; Suhendra, Lutfi; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
This research aims to determine the effect of temperature and time of stirring on a basis cream and determine the temperature and time of stir which is the best treatment for producing basis cream. This research uses a randomized block design with two factorials. The first factor is temperature which is consists of 3 levels, temperature 60 ±2 0 C, 70±2 0 C and 80±2 0 C. The second factor is the time of stirring which is consists of 3 levels 10, 15 and 20 minutes. From the combination of the two factors, were obtained of 9 experimental units. These treatments were grouped based on the time of implementation into two groups so that 18 experimental units. The observed variables are homogeneity, viscosity, adhesion, spread ability, separation ratio and pH. The data that obtained will be analyzed by analysis of variance and continued using the Tukey test. The treatment of mixing temperature and time of stirring affect the viscosity, adhesion, dispersion and separation ratio, while the treatment of mixing temperature and time of stirring did not significant effect on pH. The interaction between the two treatments can affects the adhesion, dispersion, separation ratio and pH, but not significantly affect viscosity. The treatment of mixing temperature 80±2 0 C with time of stirring 20 minutes is the best treatment to produce basis cream with characteristic viscosity cream value of 46,000 cp, a adhesion time of 17.97 seconds, spread ability of 6.50 cm, a separation ratio of 0.83 and pH 6,45. Keywords: Mixing temperature, stirring time, cream characteristics, virgin coconut oil, cocoa butter.